2012
DOI: 10.1007/s10899-012-9298-9
|View full text |Cite
|
Sign up to set email alerts
|

Gambling-Related Harms Among Adolescents: A Population-Based Study

Abstract: Internationally, and also in Europe, adolescent gambling is increasingly recognized as an important public health issue. Most research on adolescent gambling, however, is prevalence-focused and population-based studies are scarce. Few studies have examined gambling-related harms among adolescents. In a national sample, we examined self-experienced harms related to gambling and the relationship between reported harms and gambling behavior among Finnish adolescents. A national survey of 12-18-year-olds was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 11 publications
3
49
1
2
Order By: Relevance
“…There is a growing body of evidence from Europe (Kristiansen & Jensen, 2011;Luder, Berchtold, Akré, Michaud, & Surís, 2010;Olason, Skarphedinsson, Jonsdottir, Mikaelsson, & Gretarsson, 2006;Raisamo, Halme, Murto, & Lintonen, 2013), Canada and the United States (Derevensky, 2008;Derevensky, Shek, & Merrick, 2010;Huang & Boyer, 2007;Welte, Barnes, Tidwell, & Hoffman, 2009), the United Kingdom (Wardle, Moody, Spence, et al, 2011), Australia (Delfabbro, King, & Griffiths, 2014;Jackson, Dowling, Thomas, Bond, & Patton, 2008), and Asia (Liu, Luo, & Hao, 2013;Lostutter, Larimer, Neighbors, & Kaljee, 2013) indicating that young people worldwide do indeed participate in both regulated and unregulated forms of gambling, including lottery purchases (especially scratch tickets),…”
Section: Review Of Literature Youth Gamblingmentioning
confidence: 99%
“…There is a growing body of evidence from Europe (Kristiansen & Jensen, 2011;Luder, Berchtold, Akré, Michaud, & Surís, 2010;Olason, Skarphedinsson, Jonsdottir, Mikaelsson, & Gretarsson, 2006;Raisamo, Halme, Murto, & Lintonen, 2013), Canada and the United States (Derevensky, 2008;Derevensky, Shek, & Merrick, 2010;Huang & Boyer, 2007;Welte, Barnes, Tidwell, & Hoffman, 2009), the United Kingdom (Wardle, Moody, Spence, et al, 2011), Australia (Delfabbro, King, & Griffiths, 2014;Jackson, Dowling, Thomas, Bond, & Patton, 2008), and Asia (Liu, Luo, & Hao, 2013;Lostutter, Larimer, Neighbors, & Kaljee, 2013) indicating that young people worldwide do indeed participate in both regulated and unregulated forms of gambling, including lottery purchases (especially scratch tickets),…”
Section: Review Of Literature Youth Gamblingmentioning
confidence: 99%
“…Approximately 20 000 slot machines are not only available in gambling venues but in kiosks, shops, shopping centers, hotels, coffee shops, gas stations where youngsters have access into (Warpenius et al 2012). Based on a population study ( N  = 4566) conducted in 2011, 44 % of 12 to18-year-old Finns had gambled during the past 6 months (Raisamo et al 2013, 2015). Furthermore, a nationwide School Health Promotion Study ( N  = 101,167) conducted in 2010–2011 revealed that 62 % of the 14 to16-year-olds had gambled during the previous year (Räsänen et al 2015).…”
Section: Adolescent Gambling In Finlandmentioning
confidence: 99%
“…Prevalence of problem gambling reported in studies ranges from 0.2 to 12.3% among adolescents and young people aged 10 to 24 [22]. Potentially harmful effects of gambling on young people specifically include social problems, poor school performance [27, 28], and psychological distress [29, 30]. Problem gambling also has a high comorbidity with other psychological disorders, such as alcohol and substance abuse, as well as mood and anxiety disorders, and depression and internalizing disorders in general [31].…”
Section: Introductionmentioning
confidence: 99%